Comparative genomics and evolution of regulons of the LacI-family transcription factors - Ravcheev, Dmitry A.; Khoroshkin, Matvei S.; Laikova, Olga N.; Tsoy, Olga V.; Sernova, Natalia V.; Petrova, Svetlana A.; Rakhmaninova, Aleksandra B.; Novichkov, Pavel S.; Gelfand, Mikhail S.; Rodionov, Dmitry A. (Frontiers in Microbiology, 2014)
DNA-binding transcription factors (TFs) are essential components of transcriptional regulatory networks in Bacteria. LacI-family TFs (LacI-TFs) are broadly distributed among certain lineages of bacteria. The majority of characterized LacI-TFs sense sugar effectors and regulate carbohydrate utilization genes. The comparative genomics approaches enable in silico identification of TF-binding sites and regulon reconstruction. To study function and evolution of LacI-TFs, we performed genomics-based reconstruction and comparative analysis of their regulons. For over 1,300 LacI-TFs from over 270 bacterial genomes, we predicted their cognate DNA-binding motifs and identified target genes. Using the genome context and metabolic subsystem analyses of reconstructed regulons we tentatively assigned functional roles and predicted candidate effectors for 78% and 67% of the analyzed LacI-TFs, respectively. Nearly 90% of the studied LacI-TFs are local regulators of sugar utilization pathways, whereas the remaining 125 global regulators control large and diverse sets of metabolic genes. The global LacI-TFs include the previously known regulators CcpA in Firmicutes, FruR in Enterobacteria, and PurR in Gammaproteobacteria, and the three novel regulators, GluR, GapR, and PckR, that are predicted to control the central carbohydrate metabolism in three lineages of Alphaproteobacteria. Phylogenetic analysis of regulators combined with the reconstructed regulons provides a model of evolutionary diversification of LacI-TFs. The obtained genomic collection of in silico reconstructed regulons in Bacteria is available in the RegPrecise database (http://regprecise.lbl.gov). It provides a framework for future structural and functional classification of the LacI protein family and identification of molecular determinants of the DNA and ligand specificity. The inferred regulons can be also used for functional gene annotation and reconstruction of sugar catabolic networks in diverse bacteria.